Improving the quality of life of the community through the regional literacy movement - Erlin Kartikasari (Universitas Cokroaminoto Palopo, 2024)
This study investigates the relationship between the literacy movement and the quality of human life with the main aim to improve the quality of life of local communities through literacy programs initiated by local governments. Local governments must have regional regulations that regulate the implementation of education based on regional literacy movements to provide guidelines to the community in carrying out activities to improve the quality of life and welfare of local communities. This research was conducted using the literature review method with data on literacy movements that have been carried out in areas published in national journals. Improving the quality of life of the community can be done by measuring CLDI (Community Literacy Development Index) by involving two components, namely: the Community Literacy Building Element (CLBE) component and the Community Aspect (CA) component. The study found that there is a correlation between the results of good CLDI measurements and the improved quality of life of the community. Good CLDI results were obtained through regional literacy movements carried out massively in local government institutions, including: Library and Archives Office, Education and Culture Office, Community and Village Empowerment Office.